Mechanisms of Family Impact on African American Adolescents' HIV-Related Behavior - Brody, Gene H. (2011)
A longitudinal model that tested mediating pathways between protective family processes and HIV-related behavior was evaluated with 195 African American youth. Three waves of data were collected when the youth were 13, 15, and 19 years old. Evidence of mediation and temporal priority were assessed for 3 constructs: academic engagement, evaluations of prototypical risk-taking peers, and affiliations with risk-promoting peers. Structural equation modeling indicated that protective family processes assessed during early adolescence were associated with HIV-related behavior during emerging adulthood and that academic engagement, evaluations of prototypical risk-taking peers, and affiliations with risk-promoting peers accounted for this association. Evidence of a specific pathway emerged: protective family processes→academic engagement→negative evaluations of prototypical risk-taking peers→affiliations with risk-promoting peers→HIV-related behavior. Academic engagement also was a direct predictor of HIV-related risk behavior